The time course of protecting a visual memory representation from perceptual interference - van Moorselaar, Dirk; Gunseli, Eren; Theeuwes, Jan; N. L. Olivers, Christian (Frontiers in Human Neuroscience, 2015)
Cueing a remembered item during the delay of a visual memory task leads to enhanced recall of the cued item compared to when an item is not cued. This cueing benefit has been proposed to reflect attention within visual memory being shifted from a distributed mode to a focused mode, thus protecting the cued item against perceptual interference. Here we investigated the dynamics of building up this mnemonic protection against visual interference by systematically varying the SOA between cue onset and a subsequent visual mask in an orientation memory task. Experiment 1 showed that a cue counteracted the deteriorating effect of pattern masks. Experiment 2 demonstrated that building up this protection is a continuous process that is completed in approximately half a second after cue onset. The similarities between shifting attention in perceptual and remembered space are discussed.